2020
DOI: 10.3389/fphar.2020.00128
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Protects Against Lipopolysaccharide-Induced Acute Kidney Injury by Enhancing Autophagy Through Inhibition of the PI3K/AKT/mTOR Pathway

Abstract: Background: Acute kidney injury (AKI) is often secondary to sepsis. Previous studies suggest that damaged mitochondria and the inhibition of autophagy results in AKI during sepsis, but dexmedetomidine (DEX) alleviates lipopolysaccharide (LPS)-induced AKI. However, it is uncertain whether the renoprotection of DEX is related to autophagy or the clearance of damaged mitochondria in sepsis-induced AKI. Methods: In this study, AKI was induced in rats by injecting 10 mg/kg of LPS intraperitoneally (i.p.). The rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 38 publications
6
80
1
Order By: Relevance
“…extract decreased the inflammatory response and OS via activation of the Akt signaling pathway in an LPS-shock mouse model ( 60 ). Zhao et al ( 61 ) reported that dexmedetomidine protected against LPS-mediated AKI in rats via inhibiting the activation of the Akt signaling pathway. Additionally, another study demonstrated that water extracts from the roots of E. purpurea containing a polysaccharide with anti-inflamma-tory properties activated the Akt signaling pathway in human acute monocytic leukemia (THP-1) cells ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…extract decreased the inflammatory response and OS via activation of the Akt signaling pathway in an LPS-shock mouse model ( 60 ). Zhao et al ( 61 ) reported that dexmedetomidine protected against LPS-mediated AKI in rats via inhibiting the activation of the Akt signaling pathway. Additionally, another study demonstrated that water extracts from the roots of E. purpurea containing a polysaccharide with anti-inflamma-tory properties activated the Akt signaling pathway in human acute monocytic leukemia (THP-1) cells ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…LC3, P62, and Beclin-1 are autophagyrelated proteins. Beclin-1 interacts with PI3K to trigger autophagy and then participates in the subsequent steps of the fusion of autophagosomes and lysosomes (Zhao et al, 2020). LC3 combines with the autophagosome membrane to form a complete autophagosome, and then fuses and degrades with lysosomes (Currarino et al, 1976).…”
Section: The Effect Of Ea Treatment On Autophagy and Apoptosis Of Neumentioning
confidence: 99%
“…Starvation or alcohol-induced autophagy usually relies on the inhibition of mammalian rapamycin target protein (mTOR), which is a key regulator of nutritional signals. In mTOR inhibition, the phosphorylation of protein complexes, including ULK1, ATG13, and RB1-coiled helix-1, is simultaneously reduced, increasing ULK1 activity and inducing autophagy [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Neuronal Death In Nddsmentioning
confidence: 99%
“…The formation of primitive phagocytic organelles or phagocytic vesicles depends on the release of Beclin1 and activating molecules present in Beclin1-regulated autophagy protein 1 from the inhibitors Bcl-2. The resulting PI3K-III complex is released from the inhibition, and this complex produces phosphatidylinosine-3-phosphate and promotes the recruitment of ATG proteins into the nascent membrane [ 69 , 71 , 72 ].…”
Section: Neuronal Death In Nddsmentioning
confidence: 99%